Contribution to discussion: MegaProgram M&E, independent evaluation arrangement - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2010)
The paper has three components. The first section discusses the important features of evaluation science and of research for development. The second section discusses options for the Independent Evaluation Arrangements regarding independence, other key considerations and cost. The third component discusses M&E of research for development in the new CGIAR.